2012
DOI: 10.1002/hep.25582
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of different interleukin-28B gene variants on the outcome of dual combination therapy in chronic hepatitis C virus type 1 infection

Abstract: In patients with chronic hepatitis C virus (HCV) infection, several variants of the interleukin-28B (IL28B) gene have been shown to correlate significantly with a sustained virologic response (SVR). Recent evidence shows that determination of one single IL28B polymorphism, rs12979860, is sufficient for predicting treatment outcome. We examined whether the combined determination of the IL28B single-nucleotide polymorphisms (SNPs), rs12979860, rs8099917, rs12980275, and rs8103142, might improve the prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
2
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 46 publications
10
67
2
3
Order By: Relevance
“…3 Indeed, LPA levels in serum reported by Mazzocca et al were approximately 10 times higher than the previously reported LPA levels in plasma. 2,3 If their LPA values in serum were increased after sampling similarly in each sample, plasma LPA levels might be correlated with HCC burden as reported. To clarify this, we have newly measured plasma LPA levels in HCC patients,…”
Section: Plasma Lysophosphatidic Acid Levels and Hepatocellular Carcimentioning
confidence: 90%
See 3 more Smart Citations
“…3 Indeed, LPA levels in serum reported by Mazzocca et al were approximately 10 times higher than the previously reported LPA levels in plasma. 2,3 If their LPA values in serum were increased after sampling similarly in each sample, plasma LPA levels might be correlated with HCC burden as reported. To clarify this, we have newly measured plasma LPA levels in HCC patients,…”
Section: Plasma Lysophosphatidic Acid Levels and Hepatocellular Carcimentioning
confidence: 90%
“…Indeed, Italian patients have often been infected in the 1970-1980s through parenteral exposure, and as a consequence our cohort was older (mean age 55 years), more often cirrhotic (24%), and more often infected by HCV-1b (90%) than HCV patients from other geographical regions such as northern Europe. 2 Still, we cannot exclude that our relatively limited sample size might have prevented us seeing the differences observed by Fisher at al. ; however, this only strengthens the concept that the combined determination of the rs12979860 and rs8099917 genotype may hold a strong predictive power for an SVR mainly in large cohorts of patients, such as those enrolled in drug development studies, but might be less relevant at the individual level in clinical practice.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…HCV genotype 3 is the major genotype (~86%) followed by genotype 1 among thalassemic individuals in this region. Standard therapy applied to HCV patients consists of a combination of pegylated interferon (Peg-IFN) alpha 2a or b and ribavirin (RBV) for 24-48 weeks depending upon HCV genotype, viremia as well as host factors such as IL28B genotype, age, sex, race and liver fibrosis status [10]. But the response rates in HIV/HCV co-infected thalassemic individuals were very poor (unpublished data).…”
Section: Therapy Of Hepatitis C In Hiv Co-infected Patientsmentioning
confidence: 99%